2020
DOI: 10.1038/s41598-020-75083-9
|View full text |Cite
|
Sign up to set email alerts
|

Loss of RBMS1 as a regulatory target of miR-106b influences cell growth, gap closing and colony forming in prostate carcinoma

Abstract: Prostate carcinoma (PCa) is the second most commonly diagnosed cancer in males worldwide. Among hereditary genetic mutations and nutrient factors, a link between the deregulation of microRNA (miRNA) expression and the development of prostate carcinoma is assumed. MiRNAs are small non-coding RNAs which post-transcriptionally regulate gene expression and which are involved in tumour development and progression as oncogenes or tumour suppressors. Although many genes could be confirmed as targets for deregulated m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…In this study, hsa-miR-106b-5p, hsa-miR-17-5p and hsa-miR-183-5p were identified to construct a miRNA-mRNA regulatory network of prostate cancer. Hsa-miR-106b-5p, as an oncogene, may down-regulate RBMS1 expression in prostate cancer tissues and affect cell proliferation, gap closure and colony formation (20). Meanwhile, hsa-miR-106b in the blood of prostate cancer patients is significantly higher than that of healthy controls (21).…”
Section: Discussionmentioning
confidence: 98%
“…In this study, hsa-miR-106b-5p, hsa-miR-17-5p and hsa-miR-183-5p were identified to construct a miRNA-mRNA regulatory network of prostate cancer. Hsa-miR-106b-5p, as an oncogene, may down-regulate RBMS1 expression in prostate cancer tissues and affect cell proliferation, gap closure and colony formation (20). Meanwhile, hsa-miR-106b in the blood of prostate cancer patients is significantly higher than that of healthy controls (21).…”
Section: Discussionmentioning
confidence: 98%
“…The RBMS1 gene is located at chromosome 2q24.2, and it encodes for a protein that binds single stranded DNA/RNA and plays an important role in DNA replication, cell cycle progression, gene transcription, and apoptosis. A recent study demonstrated that the RBMS1 locus acts by regulating the expression of the miR-106b [105], which has been found overexpressed in hepatocellular carcinoma [106], cervical cancer [107], renal carcinoma [108], and gastric cancer [109]. At the same time, Dankert and collaborators have also demostrated that miR-106b can regulate endogenous RBMS1 expression in PCa cell lines and, thereby, act as a tumor suppressor gene with inhibitory effects on colony formation and cell growth [105].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that the RBMS1 locus acts by regulating the expression of the miR-106b [105], which has been found overexpressed in hepatocellular carcinoma [106], cervical cancer [107], renal carcinoma [108], and gastric cancer [109]. At the same time, Dankert and collaborators have also demostrated that miR-106b can regulate endogenous RBMS1 expression in PCa cell lines and, thereby, act as a tumor suppressor gene with inhibitory effects on colony formation and cell growth [105]. Despite the lack of evidence linking RBMS1 SNPs and risk of PCa, it seems to be plausible to suggest that the presence of genetic variants in the RBMS1 locus might control miR-106b levels and, therefore, favors tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Higher expression of miR-106b leads to loss of RBMS1 and influenced the cell growth, colony formation, and gap closing in prostate cancer tissue/cells. 68 …”
Section: Prostate Cancermentioning
confidence: 99%